Biogas and bio-fertilizer production potential of abattoir waste: implication in sustainable waste management in Shashemene City, Ethiopia - Tamiru Kefalew; Misgana Lami (Heliyon, 2021)
Fossil fuel resources become scarce, and their combustion is a major pollutant in the environment. As a result, scientists are eager to find alternatives to fossil fuels, and biomass could be one of them. One method of turning biomass into biogas is anaerobic digestion (AD). One of the organic waste kinds used to generate biogas is abattoir waste. In developing countries, managing abattoir waste streams is a significant concern. Using these wastes to produce biogas and biofertilizers could help Ethiopia reduce its environmental hazard while also solving energy and fertilizer-related issues. Given that, the researchers in this study intend to investigate the biogas and bio-fertilizer production potential of abattoir waste in Shashemene Municipality Abattoir (SMA), Ethiopia. To this aim, the production potential of biogas, energy, biofertilizer, and Greenhouse gas (GHG) reduction was examined. The study showed about 688,755 kg (kg) per year of slaughterhouse waste is produced from 13,505 cattle, and anaerobic digestion may create approximately 206.63 × 103 m3/year of biogas. As a result, it can generate 1,018.98 Kilowatt-hour (kWh)/day and 371,927.7 kWh/year. On an annual basis, the biogas output (206.63 103 m3) can replace the 211.8 tons of energy consumed by LPG, kerosene, charcoal, furnace oil, petrol, and diesel. Moreover, the anaerobic digester has the potential to minimize the emission of greenhouse gas (GHG) by 952.4 tons CO2 eq per year. Furthermore, biogas has the potential to generate 43,184.9 kg of dry bio-fertilizer per year. Therefore, while biogas technology is the long-term solution for ensuring environmental safety and public health, proper disposal was one of the short-term options.